2017
DOI: 10.1007/s10646-017-1764-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of petroleum-derived substances on life history traits of black bean aphid (Aphis fabae Scop.) and on the growth and chemical composition of broad bean

Abstract: The aim of the study was to determine the effects of various petroleum-derived substances, namely petrol, diesel fuel and spent engine oil, on life history traits and population dynamics of the black bean aphid Aphis fabae Scop. and on growth and chemical composition of its host plant Vicia faba L. Each substance was tested separately, using two concentrations (9 g kg−1 and 18 g kg−1). The experiment was conducted in four replications (four pots with five plants in each pot per treatment). Plants were cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 56 publications
7
29
2
Order By: Relevance
“…Davies et al [41] found that, under laboratory conditions, the larvae of black bean aphids reach sexual maturity as early as after 5.85 ± 0.35 days; however, under field conditions, this period is usually extended and is generally between 7.65 and 11.3 days [18,40]. In our studies, the period amounted to 11.13 days for the first generation, and 9.25 days for the second generation.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Davies et al [41] found that, under laboratory conditions, the larvae of black bean aphids reach sexual maturity as early as after 5.85 ± 0.35 days; however, under field conditions, this period is usually extended and is generally between 7.65 and 11.3 days [18,40]. In our studies, the period amounted to 11.13 days for the first generation, and 9.25 days for the second generation.…”
Section: Discussioncontrasting
confidence: 47%
“…In our studies, the period amounted to 11.13 days for the first generation, and 9.25 days for the second generation. The fecundity of the wingless females of A. fabae foraging on broad bean plants ranges between 15.3 to 59.2 larvae born [37,42], and their lifespan amounts to 16-25 days [18,40,42,43]. In our experiment, the females foraging on control plants gave birth to an average of approximately 29 larvae, and their lifespan was approximately 16-18 days.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, they were often observed burrying themselves in the soil, which exposed them to contact with petroleum compounds through integuments. There is a considerable diversification in the response to oil derivatives depending on animal species and age [32,33]. Considering their survival rate, adult earthworms are much more resistant to oil derivatives than their juvenile forms or Collembola.…”
Section: Resultsmentioning
confidence: 99%